ANATOMICAL STRUCTURE OF THE AORTA AND MAJOR ARTERIES AND THEIR HEMODYNAMIC SIGNIFICANCE (International journal of medical sciences, 2025)
This study provides a detailed review of the anatomical structure and hemodynamic function of the aorta and major systemic arteries, including the carotid, subclavian, renal, and iliac arteries. It emphasizes how specific morphological features—such as lumen diameter, wall thickness, histological composition, and elasticity—directly influence blood flow dynamics, vascular resistance, and regional organ perfusion. The analysis highlights the functional significance of elastic arteries, particularly the aorta, in buffering cardiac pulsations and maintaining continuous diastolic flow, as well as the role of muscular arteries, such as the renal and iliac arteries, in regulating regional blood flow through vasomotor control. Additionally, the study explores how variations in arterial geometry, including branching patterns and bifurcation points, affect shear stress distribution and contribute to the localization of vascular pathologies, including atherosclerosis and aneurysm formation. By integrating anatomical and physiological perspectives, this research underscores the clinical relevance of understanding arterial structure–function relationships for the early detection, prevention, and management of cardiovascular diseases.